2005
DOI: 10.1115/1.1852494
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Water-Cooled Silicon Carbide Milli-Channel Heat Sinks for High Power Electronic Applications

Abstract: Heat transfer and fluid flow in a novel class of silicon carbide water-cooled milli-channel heat sinks were investigated. The heat sinks were manufactured using an extrusion freeform fabrication (EFF) rapid prototyping technology and a water-soluble polymer material. Rectangular heat exchangers with 3.2 cm×2.2 cm planform area and varying thickness, porosity, number of channels, and channel diameter were fabricated and tested. The perchannel Reynolds number places the friction coefficients in the developing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Bower et al [22] presented experimental results on the heat transfer and flow in small SiC heat exchangers with multiple rows of parallel channels oriented in the flow direction. They analyzed the overall heat transfer and pressure drop coefficients in single-phase flow regimes and found that liquid-cooled SiC heat sinks easily outperform air-cooled heat sinks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bower et al [22] presented experimental results on the heat transfer and flow in small SiC heat exchangers with multiple rows of parallel channels oriented in the flow direction. They analyzed the overall heat transfer and pressure drop coefficients in single-phase flow regimes and found that liquid-cooled SiC heat sinks easily outperform air-cooled heat sinks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bower et al [22] presented experimental results on the heat transfer and flow in small SiC heat exchangers with multiple rows of parallel channels oriented in the flow direction. They analyzed overall heat transfer and pressure drop coefficients in single phase flow regimes and found that liquid-cooled SiC heat sinks easily outperform air-cooled heat sinks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nakayama [9] clearly brings out the superiority of direct water cooling, especially in conjunction with microchannels. The use of external heat sinks with liquid cooled microchannels has also been extensively studied in the literature (e.g., Missaggia et al [10] and Bower et al [11]).…”
Section: Direct Cooling With Water-design Considerationsmentioning
confidence: 99%